Prediction model of PTO shaft fatigue damage considering sandy loam and loam in rotary-tillage operation - Moon-Kyeong Jang; Seung-Jun Kim; Young-Hoo Cho; Ju-Seok Nam (Journal of Agricultural Engineering)
In this study, the fatigue damage to a power takeoff (PTO) shaft was evaluated under various operating conditions in rotary-tillage operations, considering soil strength and texture. Pearson correlation analysis was conducted to identify the significant variables influencing PTO shaft fatigue damage, and a prediction formula was derived through regression analysis using these variables. The PTO shaft exhibited increased shear stress with higher transmission gear stages, PTO gear stages, or soil properties, including strength and texture. The fatigue damage increased with higher transmission gear stages and soil strength while decreasing with higher PTO gear stages. Notably, as the PTO gear stage increased, the mean stress increased; however, the stress amplitude and equivalent completely reversed stress significantly reduced fatigue damage. Statistical analyses revealed a strong correlation between PTO shaft fatigue damage and factors such as tractor travel speed, PTO shaft power consumption, PTO shaft rotational speed properties, including strength and texture. The developed prediction equation, incorporating all significant variables, demonstrated, with a coefficient of determination (R²) of 0.93 and a root mean square error (RMSE) of 2.94×10-9. This equation effectively identifies trends in PTO shaft fatigue damage based on key operational variables. Furthermore, the findings emphasize the critical role of soil texture in assessing PTO shaft fatigue damage.